Propagation Cadre Training by the Islamic Boarding School Development Bureau as an Effort to Improve Public Speaking During Sarwahan Activities - Shalshabila, Mutiara Alif (Journal of Educational Management Research, 2025)
This study aims to analyze the implementation of the Preaching Cadre Training as an effort to improve students' public speaking skills through the Sarwahan activity. Employing a descriptive qualitative approach, data were collected through observation, interviews, and documentation related to the training process and students' preaching practices. The findings indicate that this training, based on experiential learning, significantly enhances students' self-confidence, public speaking competence, and active participation in Sarwahan forums. Sarwahan has proven effective as a contextual and practical preaching training medium that supports the development of communicative character among students. However, the program faces challenges, including low participant commitment and limited external communication media. Therefore, strengthening training strategies and managerial support such as optimizing digital media and providing intensive mentorship is essential. These findings are expected to contribute to the development of an adaptive and sustainable Islamic boarding school-based preaching training model.